AN ERROR ANALYSIS ON THE ENGLISH DIRECT AND INDIRECT SPEECH IN THE PAST TENSE FORM - Budiwaty, Suci (Universitas Gunadarma, 2013)
This research is analyzing errors made by the students in answering the past tense form of English direct and indirect speech. The aim of this research is to find out how many errors made by the students in answering the questions of English direct and indirect speech in the past tense form.The population is the first year students of the faculty of Economy majoring Accounting,Gunadarma University, namely lEB 11 and 1EB13. The number of population is 88 students which is 43 students from 1EB11 and 45 students from 1EB13.50 students are choosen as the sample. The data analysis will show the result of the occurence of errors made by the sample by giving the numbers of students who made errors, then giving the explanation of the correct answer, and interpreting the data. The result shows that most students still found difficulties in answering the questions. Errors happened more in changing the sentence from the direct speech to indirect speech in the form of simple past than in the form of past perfect tense.